Growth curve of the perennial ryegrass and common vetch association - Bello Olivera, Benito; Mendoza Pedroza, Sergio Iban; Sosa Montes, Eliseo; Bárcena Gama, José Ricardo; Pro Martínez, Arturo; Zambrano Velasco, María Guadalupe (Revista Mexicana de Ciencias Agrícolas, 2022)
Annual species generate establishment costs several times per year, perennial grasslands allow the initial investment to be amortized for two or more years; however, perennial species have a slow establishment and compete with undesirable weeds, so the present research work aims to determine the yield of a perennial ryegrass (Lolium multiflorum L.) and common vetch (Vicia sativa L.) association. The study was conducted in the experimental field ‘Predio Nuevo’ of the College of Postgraduates, Texcoco, State of Mexico. The following variables were evaluated: dry matter (DM) content, DM yield, leaf:stem ratio, dead material, weeds and intercepted radiation. The first sampling was at 38 days, after that they were made every 14 days until 150 days when a mechanical cut was made, two subsequent cuts were made every 28 days. A progressive increase was observed as age progressed until 150 days (10 052 kg DM ha-1), as well as 6 331 kg DM ha-1 and 6 397 kg DM ha-1 for the second and third cuts. The DM increased from 12.4 to 28.04% from day 38 to 150 for the first cut and to 26.67 and 27.2% for the second and third cuts. The dead material was observed on day 80 with 0.84%, the value reached 17.3% for day 150. The association of perennial ryegrass and common vetch increases DM yield at the first cut without affecting the subsequent yields of the perennial crop.
Keywords: forage; grassland; yield